Acute postoperative pain management. Issue 2 (5th January 2020) - Small, C.; Laycock, H.
Abstract : Background: Acute postoperative pain is common. Nearly 20 per cent of patients experience severe pain in the first 24 h after surgery, a figure that has remained largely unchanged in the past 30 years. This review aims to present key considerations for postoperative pain management. Methods: A narrative review of postoperative pain strategies was undertaken. Searches of the Cochrane Library, PubMed and Google Scholar databases were performed using the terms postoperative care, psychological factor, pain management, acute pain service, analgesia, acute pain and pain assessment. Results: Information on service provision, preoperative planning, pain assessment, and pharmacological and non‐pharmacological strategies relevant to acute postoperative pain management in adults is presented, with a focus on enhanced recovery after surgery pathways. Conclusion: Adequate perioperative pain management is integral to patient care and outcomes. Each of the biological, psychological and social dimensions of the pain experience should be considered and understood in order to provide optimum pain management in the postoperative setting. Abstract : Pain controllable Abstract : Antecedentes: El dolor agudo postoperatorio es frecuente. Casi el 20% de los pacientes experimentan dolor intenso durante las primeras 24 horas después de la cirugía, una cifra que se ha mantenido prácticamente sin cambios en los últimos 30 años. Esta revisión tiene como objetivo presentar las consideraciones clave a tener en cuenta en el tratamiento del dolor postoperatorio. Métodos: Se realizó una revisión descriptiva de las estrategias para el tratamiento del dolor postoperatorio. Se efectuó una búsqueda bibliográfica en las bases de datos Cochrane Library, PubMed y Google Scholar utilizando los términos: 'cuidado postoperatorio' ( postoperative care ); 'factor psicológico' ( psychological factor ); 'tratamiento del dolor' ( pain management ); 'servicio de dolor agudo' ( acute pain service ); 'analgesia' ( analgesia ); 'dolor agudo' ( acute pain ); y 'evaluación del dolor' ( pain assessment ). Resultados: En el tratamiento del dolor agudo postoperatorio en adultos son relevantes: la prestación de servicios, la planificación preoperatoria, la evaluación del dolor y los tratamientos farmacológicos y no farmacológicos haciendo énfasis en los programas de rehabilitación multimodal tras la cirugía. Conclusión: El tratamiento adecuado del dolor perioperatorio es parte integral en la atención del paciente y en los resultados obtenidos. Se deben considerar y entender cada una de las dimensiones biológica, psicológica y social del dolor para proporcionar un tratamiento óptimo durante el postoperatorio.